2022
DOI: 10.1021/acs.jproteome.2c00251
|View full text |Cite
|
Sign up to set email alerts
|

Prevaccination Glycan Markers of Response to an Influenza Vaccine Implicate the Complement Pathway

Abstract: A key to improving vaccine design and vaccination strategy is to understand the mechanism behind the variation of vaccine response with host factors. Glycosylation, a critical modulator of immunity, has no clear role in determining vaccine responses. To gain insight into the association between glycosylation and vaccine-induced antibody levels, we profiled the pre- and postvaccination serum protein glycomes of 160 Caucasian adults receiving the FLUZONE influenza vaccine during the 2019–2020 influenza season us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Glycosylation of human immune system proteins also has an impact on vaccine response, and in future might be considered in the selection of vaccine recipients. Findings from a recent study suggest that postvaccination protection is partly dependent on modulation of glycosylation by the human immune system [ 68 ].…”
Section: Roles Of Na and Glycosylation In Immunity And Potential For ...mentioning
confidence: 99%
“…Glycosylation of human immune system proteins also has an impact on vaccine response, and in future might be considered in the selection of vaccine recipients. Findings from a recent study suggest that postvaccination protection is partly dependent on modulation of glycosylation by the human immune system [ 68 ].…”
Section: Roles Of Na and Glycosylation In Immunity And Potential For ...mentioning
confidence: 99%
“…High-throughput glycomic analysis using our established array technology has revealed new roles for glycans in cancer biology, 17 host–pathogen interactions, 18 , 19 and vaccine response. 20 In brief, each sample was fluorescently labeled ( S , Alexa Fluor 555 labeled) and mixed with an equal amount of an orthogonally labeled reference standard ( R , Alexa Fluor 647 labeled commercial plasma). Samples were analyzed using in-house fabricated lectin microarrays containing >95 probes ( Tables S4 and S5 ), as previously described.…”
Section: Resultsmentioning
confidence: 99%
“…An advantage of this method is that probes that identify significant changes in the glycome can then be used for further glycoproteomic and histochemical studies. High-throughput glycomic analysis using our established array technology has revealed new roles for glycans in cancer biology, host–pathogen interactions, , and vaccine response . In brief, each sample was fluorescently labeled ( S , Alexa Fluor 555 labeled) and mixed with an equal amount of an orthogonally labeled reference standard ( R , Alexa Fluor 647 labeled commercial plasma).…”
Section: Resultsmentioning
confidence: 99%
“…As the inflammatory response intersects with the complement system described here ( Figure 3 ), the study confirms our findings. Another study found that proteins of the complement system are among the top proteins with a significant glycan Le a difference between low and high flu vaccine responders, implying that indeed the complement system affects the vaccine response [24].…”
Section: Discussionmentioning
confidence: 99%
“…One study examined the transcriptome in human PBMCs and showed that the expression of nine genes is associated with seroconversion against the flu vaccine after adjusting for the baseline antibody titers [23]. A more recent study using lectin microarrays and glycoproteomics found that the serum glycan Le a is associated with the serological response to the flu vaccine, and further, that Le a -binding proteins are enriched in the complement system [24].…”
Section: Introductionmentioning
confidence: 99%